Self-Assembly of DNA molecules in magnetic Fields. (18th November 2021) - Gao, Mingyan; Hu, Jing; Wang, Jianfei; Liu, Mengnan; Zhu, Xiaona; Saeed, Sadaf; Hu, Cuihua; Song, Zhengxun; Xu, Hongmei; Wang, Zuobin
Abstract: In this work, a rich variety of self-assembled DNA patterns were obtained in the magnetic field. Herein, atomic force microscopy (AFM) was utilized to investigate the effects of the concentration of DNA solution, intensity and direction of magnetic field and modification of mica surface by different cations on the self-assembly of DNA molecules. It was found that owning to the change of the DNA concentration, even under the same magnetic field, the DNA self-assembly results were different. The in situ test results showed that the DNA self-assembly in an magnetic field was more likely to occur in liquid phase than in gas phase. In addition, whether in a horizontal or vertical magnetic field, a single stretched dsDNA was obtained in a certain DNA concentration and magnetic field intensity. Besides, the modification of cations on the mica surface significantly increased the force between the DNA molecules and mica surface, and further changed the self-assembly of DNA molecules under the action of magnetic field.